2022
DOI: 10.3390/rs14030674
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy of Forest Phenological Extraction from Sentinel-1 C-Band Backscatter Measurements in Deciduous and Coniferous Forests

Abstract: Satellite remote sensing is an important method for forest phenological studies at continental or global scales. Sentinel-1 (S1), a polar orbit satellite with a spatial resolution of 10 m, provides an opportunity to observe high-resolution forest phenology. The sensitivities of S1 C-band backscatter measurements to vegetation phenology, such as crops, meadows, and mixed forests, have been discussed, whereas their performance for different forest types has not yet been quantitatively assessed. It is necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Our study revealed the seasonal change in CR time series. Previous studies, such as Ling, et al [32], extracted forests phenology based on seasonally changed CR time series. In this study, we related the variation of CR with the variation of structure and water content during the growth of deciduous forests (Fig.…”
Section: A Physiological Drivers Of Seasonal Changes In Cr In Deciduo...mentioning
confidence: 99%
See 3 more Smart Citations
“…Our study revealed the seasonal change in CR time series. Previous studies, such as Ling, et al [32], extracted forests phenology based on seasonally changed CR time series. In this study, we related the variation of CR with the variation of structure and water content during the growth of deciduous forests (Fig.…”
Section: A Physiological Drivers Of Seasonal Changes In Cr In Deciduo...mentioning
confidence: 99%
“…The process of determining the threshold fully considered the asynchronism between the variation of the woody water content and the variation of leaf greenness of deciduous forests. Previous study on forests phenology used the same threshold to extract phenology from SAR and optical data [32], without considering the unique characteristics of CR and NDVI. Moreover, our study was carried out based on 41 PhenoCam deciduous forests sites in the eastern United States, rather than based on few sites [32].…”
Section: Sos Maps Derived From Satellite Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Plants as ecosystem producers are the most sensitive to climate change, of which phenology is one of the most important indicators, plant phenology is the phenomenon of periodic changes in plants under the influence of natural conditions such as climate, soil and topography. Plant phenology research mainly includes two approaches, one is through observing and recording the periodic growth and development rhythm of plants such as germination, leaf spreading, flowering, fruiting, leaf falling, withering and wilting at the species scale 6 , the second is remote sensing phenology (RSP), which use various remotely sensed vegetation indexes to determine the start of growing season (SOS), end of growing season (EOS) and length of growing season (LOS) et al at the regional scale 7 .…”
mentioning
confidence: 99%